The Role of Digitalization in Ensuring the Financial and Economic Security of Trading Enterprises Under the Conditions of External Shocks. - Вербівська, Людмила Василівна (International Journal of Safety and Security Engineering., 2023)
This study investigates the role of digitalization in preserving the financial stability of trading enterprises amidst rapid and unpredictable economic shocks, with a specific focus on Ukraine, a country frequently undergoing socio-political crises and conflicts with the Russian Federation. Through an in-depth exploration of the theoretical constructs of these businesses, the unique characteristics of their operations and behavior in stable and turbulent conditions are delineated. The impact of contemporary information and communication technologies on the performance of trading enterprises, particularly under challenging management conditions, is scrutinized. Empirical evidence from Ukrainian trading enterprises during crisis periods is analyzed to elucidate the practical implications of their operations under such conditions. A comprehensive examination of recent national economic trends within Ukraine and, by extension, its trading sector, is carried out. Econometric modeling is employed to further clarify the role of this sector in shaping economic progress. The study underscores the significance of digitalization in the operations of trading enterprises. The results demonstrate that digitalization not only bolsters efficiency but also enhances resilience, particularly under unforeseen circumstances. The adoption of digital technologies affords these enterprises new product sales avenues, timely settlement with business partners, and sustenance of their own activities.
Maksym Dubyna, Liudmyla Verbivska, Olha Kalchenko, Veronika Dmytrovska, Dmytro Pilevych, Іhor Lysohor. The Role of Digitalization in Ensuring the Financial and Economic Security of Trading Enterprises Under the Conditions of External Shocks. International Journal of Safety and Security Engineering. Vol. 13, No. 5, October, 2023, pp. 821-833
Keywords: trading enterprise, digitalization, trade relations, digital communication links, digital communication channels, national economy, financial and economic security, competitiveness, stochastic development